Re-examining the center of gravity: Theoretical and structural analysis of the concept - Šlebir, Miha (Revista científica "General José María Córdova.", 2022)
The center of gravity concept is one of contemporary military science’s fundamental yet highly controversial pillars. Although, over the past decades, the center of gravity has become the modus operandi of the planning and conduct of (major) military operations in a number of armed forces, the concept remains insufficiently understood and is often poorly applied in practice. In this light, we have sought to improve its theoretical comprehension by identifying the conceptual dimensions that the most influential authors commonly highlight. Using the structural method for the concept analysis, we have identified seven entities frequently understood as the potential centers of gravity. These are: (1) fielded military, (2) leadership, (3) industry, (4) infrastructure, (5) population, (6) public opinion, and (7) ideology.